<DATA REPORT>RECORDS OF RADIO AURORA AT SYOWA STATION, ANTARCTICA IN 1985 - IGARASHI, Kiyoshi; MAENO, Hideo; OGAWA, Tadahiko (National Institute of Polar Research, 1987)
P(論文) departmental bulletin paper